Professional Teachers’ Learning Management in Enhancing Students’ Learning Interest and Motivation at SDN 1 Tanjung Kemala - Danang Pandu Aji; Sofwan Adiputra; Siswoyo (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2026)
The study aims to describe and analyze professional teachers’ learning management in improving students’ learning interest and motivation at SDN 1 Tanjung Kemala, Pugung District, Tanggamus Regency. A qualitative approach with a descriptive research design was employed. The research subjects consisted of the vice principal and professional teachers, while the research object was teachers’ learning management. Data were collected through in-depth interviews, observations, and documentation studies, and were analyzed thematically. The findings reveal that lesson planning has been developed in accordance with the curriculum; however, the analysis of students’ needs, interests, and characteristics has not been optimal. The organization of learning resources, including the use of instructional media and supporting facilities, remains limited. In the implementation stage, teachers have applied a variety of teaching methods, yet conventional approaches still dominate classroom practices. Learning evaluation has been conducted, but follow-up actions based on evaluation results have not been implemented consistently. Overall, professional teachers’ learning management contributes to improving students’ learning interest and motivation, but it still requires strengthening in student-centered planning, instructional innovation, and continuous evaluation. Keywords: Learning Management, Teachers, Students Motivation and Interest.